2004
DOI: 10.1016/j.jacc.2003.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem molecular screening in unexplained sudden death

Abstract: In this autopsy series, only 2 of 12 patients with unexplained sudden death were observed to have a defect in HERG among five candidate genes tested. It is likely that elucidation of SCD mechanisms in such patients will await the discovery of multiple, novel arrhythmia-causing gene defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(90 citation statements)
references
References 32 publications
0
84
1
1
Order By: Relevance
“…[2][3][4] We have also examined the possible mutations of genes responsible for long QT syndrome, and found 1 case possessing a novel mutation of KCNQ1, which encodes a cardiac voltage-dependent K + channel (unpublished data). Whether the mutation was really involved in the cause of death in the victim is still being investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] We have also examined the possible mutations of genes responsible for long QT syndrome, and found 1 case possessing a novel mutation of KCNQ1, which encodes a cardiac voltage-dependent K + channel (unpublished data). Whether the mutation was really involved in the cause of death in the victim is still being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1 Fatal arrhythmia has been suggested as being involved in the etiology of SUD. [2][3][4] Recent progress in postmortem molecular analysis has revealed that mutations of the cardiac ryanodine receptor type 2 (RyR2) gene are involved in some cases of SUD. 5 The RyR2 gene, encompassing 105 exons, encodes a Ca 2+ channel, which is localized across the sarcoplasmic reticulum (SR) membrane of cardiomyocytes.…”
mentioning
confidence: 99%
“…Channelopathies are dysfunctional myocyte ion channels that result in abnormal movement of electrolytes into and/or out of the cell and predispose the heart to arrhythmia. [492][493][494][495][496][497][498][499][500][501] Mutations causing cardiac ion channelopathies are found in 2% to 10% of victims [492][493][494][495][496][497][498] and in 14% to 20% of young adults with sudden death in whom the cause of death is not evident in a routine autopsy. 499 -501 Clinical and laboratory (eg, ECG, molecular-genetic screening) investigations of first-and second-degree relatives of patients with sudden unexplained death reported inherited, arrhythmogenic disease in 22% to 53% of families.…”
Section: Sudden Unexplained Deathsmentioning
confidence: 99%
“…Los estudios moleculares de MSC incluyen la detección de genoma viral en las miocardiopatías inflamatorias y el análisis de mutaciones genéticas en enfermedades cardíacas estructurales y no estructurales determinadas genéticamente [1,7,8,26]. Para este propósito, 10 ml de sangre con EDTA y 5 g de tejido cardíaco y esplénico son congelados y conservados a -80 ºC o, como alternativa, guardados en RNA later a 4 ºC hasta un período de 2 semanas.…”
Section: Patología Molecularunclassified